Technologie informatyczne neuronauk w przekazie medialnym - Osiński, Grzegorz (Fides, Ratio et Patria. Studia Toruńskie, 2018)
Technological changes in the modern media coverage require the use of advanced computer technologies. The usage of interaction and the dominance of visual components caused necessary using artificial intelligence (AI) algorithms. The AI algorithms are used at all stages of the preparation of media coverage and in studies of its impact on recipients. Appropriate adaptation of AI methods to dynamic media transmission uses Brain Computer Interfaces (BCI) technologies. Experimental research with the BCI technologies may indicate a new direction of development and improvement of contemporary forms of media coverage.